Land Use and Changes in Soil Morphology and Physical-Chemical Properties in Southern Amazon - Melo,Vander Freitas (2017)
ABSTRACT Many Amazonian farmers use the slash-and-burn method rather than fertilization for crop production. The aim of the present study was to evaluate changes in the morphological, physical, and chemical properties of naturally fertile Inceptisols after conversion from native forest to different uses in southern Amazonia, Brazil. Land covered by dense native forest (NF) was split into four areas of 1.0 ha each. Three areas were slashed and burned and then cultivated for 11 years with coffee (CO), secondary forest (SF), and pasture (PA). Four soil profiles were sampled in each treatment (four uses × four replicates). The mean value distribution of each physical and chemical analysis was determined for different depths, and standard error bars were placed to display significant differences among treatments. Results showed that morphology and physical properties were negatively affected after the establishment of PA and CO: a reduction in the thickness of the A horizon and in aggregate stability, a decrease in total porosity and macroporosity, and an increase in aggregate size and bulk density. Soil bulk density (SBD), geometric mean diameter of water-stable aggregates (GMD), and microporosity (SMi) were higher in soil under pasture as a consequence of more intense soil surface compaction. Native and secondary forests were the only treatments that showed granular structures in the A horizon. Significant differences between native forest and secondary forest were mainly found in the top soil layer for total porosity (STP) (NF>SF), macroporosity (SMa) (NF>SF), SBD (NF>SF) and GMD (SF>NF). Phosphorus contents in the A horizon increased from 6.2 to 21.5 mg kg-1 in PA and to 27.2 mg kg-1 in SF. Soil under coffee cultivation exhibited the lowest levels of Ca2+ and sum of bases in surface horizons. In all slash-and-burn areas there was a reduction in the C stock (Mg ha-1) of the A horizon: native forest 6.3, secondary forest 4.5, pasture 3.3, and coffee 3.1.